For Want of a Nail - Vogler, Candace (Christian bioethics, 2008)
In “Modern Moral Philosophy,” Elizabeth Anscombe charged that Sidgwick's failure to distinguish intended from merely foreseen consequences of an action counted as a very bad degeneration of thought. Sidgwick's failure is endemic to contemporary normative models of decision and choice. There are three components to rational decision making on these models: what the agent wants the prospective actions or policies under consideration and what the agent expects will happen as a result of taking specific action or adopting specific policy measures. The prospective actions are often modeled as lotteries across possible outcomes. Choice on any lottery-based model or representation is choice among probability distributions. Participants in contemporary risk assessment studies do not make decisions in the way suggested by these models. Instead, the participants deploy a distinctive form of estimating the future. I advance a series of considerations meant to motivate the claim that the form of estimating the future at issue for participants of risk assessment studies may be sound, even when the content of their practical judgment is dubious. The form belongs equally to ethics and to practical reason and tracks Anscombe's remarks about moral responsibility.